2017
DOI: 10.3998/mjcsloa.3239521.0023.205
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Student Motivations for Service-Learning: An Application of the Volunteer Functions Inventory

Abstract: This study extends a line of research focused on motivational factors that contribute to first-year students' reasons for engaging in service-learning. Among first-year students, altruistically-motivated students (Christensen, Stritch, Kellough, & Brewer, 2015) and minority students (Pearl & Christensen, 2016) were not only more knowledgeable of service-learning upon entering college but they were also more interested in enrolling in service-learning. The present study employs the Volunteer Functions Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 29 publications
3
25
3
Order By: Relevance
“…_____ Students are asked to reflect on their own values and identity as part of the service project. (Christensen, Stritch, Kellough, & Brewer, 2015) and minority students (Pearl & Christensen, 2016) were not only more knowledgeable of service-learning upon entering college but they were also more interested in enrolling in service-learning. The present study employs the Volunteer Functions Inventory (VFI) (Clary et al, 1998) …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…_____ Students are asked to reflect on their own values and identity as part of the service project. (Christensen, Stritch, Kellough, & Brewer, 2015) and minority students (Pearl & Christensen, 2016) were not only more knowledgeable of service-learning upon entering college but they were also more interested in enrolling in service-learning. The present study employs the Volunteer Functions Inventory (VFI) (Clary et al, 1998) …”
Section: Resultsmentioning
confidence: 99%
“…We fully acknowledge that this is an overly reductive view of race; however, this was necessary for the purposes of our analyses given our sample size. Through qualitative analysis, Pearl and Christensen (2016) found that minority students may be interested in fulfilling different needs by enrolling in service-learning than White students. Consequently, the first model we ran includes only race as a grouping variable, the second model includes gender as a single grouping variable, the third model includes both race and gender as grouping variables, and the final model adds the interaction of race and gender as a grouping variable.…”
Section: Analytic Methodsmentioning
confidence: 99%
See 3 more Smart Citations